Ibera Wetlands: diversity hotspot, valid ecoregion or transitional area? Perspective from a faunistic jumping spiders revision (Araneae: Salticidae) - Rubio, Gonzalo Daniel; Nadal, María Florencia; Munevar Lozano, Ana Katerinne; Avalos, Gilberto; Perger, Robert (Discovery Publication, 2020)
In the present work, the fauna of jumping spiders or Salticidae of the Iberá Wetlands was investigated. Patterns of species richness, composition and endemism in hygrophilous woodlands and savannah parklands in ten locations covering the Iberá Wetlands were analyzed. Samples were obtained using four methods: garden vacuum, pit-fall trap, beating and litter extraction. 75 species were collected, representing one third of the known Argentine salticids. Six species are recorded for the first time for Argentina. The community structure of the investigated locations suggests that the high diversity of jumping spiders is the result of the mixing of species of adjacent ecoregions such as Humid Chaco, Atlantic forest and Espinal. The transitional character of Iberá Wetlands, in combination with no endemism in nominally identified taxa, questions the ecoregion validity of Iberá for jumping spiders. The importance of taxonomy and the use of mature spiders in ecological studies is discussed.